Satisfacción del usuario de la Cooperativa de Ahorro y Crédito Salitre Ltda., agencia Vinces en el periodo 2022. - Mendoza Diaz, Kerly Jaileen (2023)
This case study entitled “User Satisfaction of the Salitre Savings and Credit Cooperative Ltda., Agencia Vinces in the period 2022”, exposes its main objective focused on the analysis of user satisfaction concerning the main problems present. in the Agency and turn the study will also focus on understanding how the quality of the service provided directly impacts the variable being studied: user satisfaction. To carry out this study, a methodological approach is used to obtain information and interpret it to issue the results concerning the data acquired. Therefore, to comply with the collection of information, it is done by applying a survey to the members of the Cooperative and in turn the main factors related to satisfaction were determined through an EFI matrix. The use of these two techniques with their respective instruments allows a better explanation of the conclusions of the case and at the same time prepares the appropriate recommendations by what is stated in the synthesis of the work, to fully comply with the conditions and guidelines established for the preparation of the present work.